2015
DOI: 10.3109/00365521.2015.1059878
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional versus Hybrid knife peroral endoscopic myotomy methods for esophageal achalasia: a case–control study

Abstract: HK in POEM can shorten the procedural time, and achieve similar treatment success compared to conventional TT knife.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…There are two possible reasons for the short procedural time: one is the high-pressure water jet, which made the submucosal injection easier than that using a conventional injection needle; the other is the ability to perform a submucosal injection and incision with one tool, which saves time in switching between the injection needle and electrosurgical knife. Tang et al [12] revealed that the use of an HK in peroral endoscopic myotomy can shorten the procedural time compared to the conventional method (injection needle and triangular tip knife), which supports our hypothesis. The biopsy size using an HK is obviously larger than that using SFF, and in cases 1 and 3, SFF was not able to collect appropriately sized biopsies.…”
Section: Discussionsupporting
confidence: 80%
“…There are two possible reasons for the short procedural time: one is the high-pressure water jet, which made the submucosal injection easier than that using a conventional injection needle; the other is the ability to perform a submucosal injection and incision with one tool, which saves time in switching between the injection needle and electrosurgical knife. Tang et al [12] revealed that the use of an HK in peroral endoscopic myotomy can shorten the procedural time compared to the conventional method (injection needle and triangular tip knife), which supports our hypothesis. The biopsy size using an HK is obviously larger than that using SFF, and in cases 1 and 3, SFF was not able to collect appropriately sized biopsies.…”
Section: Discussionsupporting
confidence: 80%
“…Although the use of several kinds of electrosurgical knives in POEM has been reported 3 13 14 , the best device has yet to be determined, with the choice of knife often depending on the endoscopist’s experience, expertise, and preference. According to previous reports, the triangle tip knife (KD-640L; Olympus Medical Systems, Japan) is most commonly used for POEM, and the HybridKnife (Erbe Elektromedizin GmbH, Tübingen, Germany), which has waterjet function, is also widely used 3 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective comparative analysis noted a shorter POEM procedure time with a hybrid knife versus a triangular tip knife (53.0 AE 17.2 vs 67.6 AE 28.4 minutes; P Z .02) but similar clinical outcomes and adverse event rates. 44 A randomized, prospective, controlled trial, comparing the hybrid knife with the water-jet system and the triangular tip knife with the conventional injection technique, reported significantly decreased procedure times with the hybrid knife (22.9 AE 6.7 vs 35.9 AE 11.7 minutes; P < .01), with no differences in clinical outcomes or adverse event rates. 19…”
Section: Comparative Studies On Technique Variationsmentioning
confidence: 99%